ANALISIS PENGARUH JENIS BEBAN LISTRIK TERHADAP KINERJA PEMUTUS DAYA LISTRIK DI GEDUNG CYBER JAKARTA - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
The development of the electricity system can not be separated from the development of the distribution system and in the development of the electric power distribution system there are some things that needs to be considered, one of which is characteristic of the load on the power distribution network. Because of the nature / characteristics of the electrical load can cause interference in the distribution system. Disorders that arise as a result of the load, these include the emergence of harmonic waves on power distribution systems.From the results of measurements that have been done on the electrical power circuit breaker (MCCB) of the fifth house obtained measured total harmonic current distortion ranged 5.8% ≤ ITHD ≤ 51%, while the calculation results ranged from 7.54% ≤ ITHD ≤ 66.1%. This data shows the fundamental current waveform distortion that exceeds the standard IEEE and IEC is 15%. The presence of current distortion harmonic waves that exceed the allowable limits on electric power distribution system will cause a disruption in the power distribution system, one of which is at the breaker electrical power trip (OFF), because of the resonance frequency caused by distortion of the current wave fundamental. Besides being able to interference with the performance of electrical power breaker, the wave harmonic distortion can cause a rise in the current and voltage on the neutral wire.